Gp130 blockade to NOD off Crohn's disease. Issue 7 (July 2021) - Mukherjee, Tapas; Philpott, Dana J.
Abstract : In a recent publication, Nayar et al . uncover specific inflammatory cell populations associated with Crohn's disease (CD) pathogenesis, and a gp130-STAT3 signaling axis linked to disease in anti-TNF antibody treatment-refractory patients. Therefore, gp130 blockade might represent a potential CD therapy approach, perhaps in conjunction with existing anti-TNF treatment regimes.